(untitled) (Physical Education, Health and Social Sciences, 2025)
The given research study is based on the topic to “To investigate the impact of managerial competencies on employee performance of healthcare professionals; in view point of employees”. Selected research objectives of the given research are to investigate the impact of managerial communication, teamwork, attentiveness and conflict management on employee performance of healthcare industry. To achieve research objectives, the researcher has used quantitative research design and deductive research approach. In addition to that, the study has used survey questionnaire as the research instrument in which questions are asked from the study participants on 5-Point Likert scale from the range of 1 to 5 for Managerial competencies and 7-Point Likert Scale from the range of 1 to 7 for Employee performance. The researcher has used primary data collection method to collect data. For the purpose of data analysis, SPSS tool is being used with the help of frequency analysis, regression and correlation technique. Population of the study are employees of Saifee Hospital, Ziauddin Hospital and Abbasi Shaheed Hospital. Sample size for this research is taken as 220. The outcomes of the given research have shown that communication and conflict management have positive insignificant correlation with employee performance. However, on the other hand, it is also found that teamwork and attentiveness are positively significantly associated with employee performance. This have a look at become conducted in a single country because of the restrictions of sources and duration. Since there were only limited observations (220 responses). Moreover, the department of the university has not allocated any budget for conducting the given research. This research study is about specific industry which is healthcare industry of Karachi and specifically Saifee Hospital, Ziauddin Hospital and Abbasi Shaheed Hospital. Therefore, other organizations can take guidance from the outcomes of this research as this research is specific to certain healthcare organizations. In addition, managers promote the teamwork and attentiveness among employees and senior management of the organization. If the researcher should have extra time than the studies would were more precise. Nevertheless, despite the fact that, we advise future studies to conduct across healthcare organizations to analyze higher comparative and proper outcomes.